Analisis Ekuitas Merek Sari Roti di Bandung - Suarna, Indri Ferdiani (EKUBIS: Jurnal Ekonomi, Keuangan, & Bisnis, 2020)
The baked goods industry in Indonesia has become increasingly competitive, so in this environment, creating and maintaining brand equity is an important strategy to maintain a competitive advantage. This study aims to empirically test and operationalize brand equity dimensions and how they interact within the context of Sari Roti brand in Bandung. A total of 480 respondents were selected by a systematic random sampling method. The questionnaire includes a set of questions intended to measure the different variables of the model. Structural Equation Modelling (SEM) was used to test the hypotheses on the brand equity model. The findings conclude that brand awareness, brand association, perceived quality and brand loyalty are influential dimensions of brand equity. The intercorrelations between perceived quality and brand association and brand loyalty, and the intercorrelations between brand awareness and brand association and brand loyalty were positive and all significant. The Sari Roti should concentrate their efforts primarily on perceived quality and brand loyalty, which have high importance and directly in the construct of brand equity. However, it should not undervalue the effects of perceived quality and brand awareness.